Asteroid and Meteorite Impacts as a Cause of Large Sedimentary Basins: A Case Study of the Transylvanian Depression - Dumitru Ioane; Irina Stanciu; Mihaela Scradeanu (Geosciences, 2025)
Impact cratering determined by collisions with meteorites and asteroids is considered one of the main natural processes in the Solar System, modifying the planets and their satellites surface during time. The Earth includes in its impact record a small number of such events due to active plate tectonics, sedimentation, and volcanism, with these geological processes destroying and burying their impact geomorphological signatures. To enlarge the Earth’s impacts database, new concepts and research methods are necessary, as well as the reinterpretation of old geological and geophysical models. Geomorphological, Geological, and Geophysical (3G) signatures in concealed impacted areas are discussed in this paper; the first offers the target characteristics, while the others give means for detecting their unseen remnants. The 3G signatures have been applied to the Transylvanian Depression, a fascinating geological structure, with difficulties in explaining the direct overlapping of regionally developed thick tuff and thick salt layers, and undecided interpretation of the regional magnetic anomaly. Large and deep sedimentary basins, such as the Precaspian, Alexandria and Transylvanian depressions, are interpreted to have started as impacted areas during the Permian or the Lower Neogene. Geophysical and geological existing information have been reinterpreted, offering a new way in understanding deeply located geological structures.